2016
DOI: 10.1259/dmfr.20150426
|View full text |Cite
|
Sign up to set email alerts
|

Movement characteristics in young patients and the impact on CBCT image quality

Abstract: Objectives: To assess patient movement characteristics in children and young adults and the impact on CBCT image quality. Methods: During 33 CBCT examinations, the patients (age: average, 14 years; range, 9-25 years) who had moved were identified by video observation [movement group (MG)]. The CBCT data sets were matched with those of 33 non-moving patients according to age, diagnostic task, examined region, field of view and voxel resolution [non-movement group (N-MG)]. Three observers scored the videos of MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…12 On the other hand, another recent study showed that axial CBCT images of impacted teeth of patients who are young with no metal in the field of view (FOV), who had been observed to move during examination, did not always present a subjectively lower quality than images originating from patients who did not move, when blindly assessed. 13 The same study showed that image quality was lower when patient movement had been observed several times during the examination, were long-lasting (i.e., longer than 5 seconds) or complex (i.e., multiplanar). 13 In any case, if patient motion artefacts are present in an image and compromise image quality, misdiagnosis may occur or a re-exposure of the patient may be decided.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…12 On the other hand, another recent study showed that axial CBCT images of impacted teeth of patients who are young with no metal in the field of view (FOV), who had been observed to move during examination, did not always present a subjectively lower quality than images originating from patients who did not move, when blindly assessed. 13 The same study showed that image quality was lower when patient movement had been observed several times during the examination, were long-lasting (i.e., longer than 5 seconds) or complex (i.e., multiplanar). 13 In any case, if patient motion artefacts are present in an image and compromise image quality, misdiagnosis may occur or a re-exposure of the patient may be decided.…”
Section: Introductionmentioning
confidence: 92%
“…13 The same study showed that image quality was lower when patient movement had been observed several times during the examination, were long-lasting (i.e., longer than 5 seconds) or complex (i.e., multiplanar). 13 In any case, if patient motion artefacts are present in an image and compromise image quality, misdiagnosis may occur or a re-exposure of the patient may be decided. 11,12 This is a major concern particularly (but not only) when the patient is a child, and 4 being a child is the major factor related to patient movement.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations